Graphene and Graphene Production
The electrochemical expansion and heat treatment of graphite using a diamond-coated cathode system effectively produces high-quality graphene flakes with controlled thickness and low defect density, addressing the limitations of existing methods and enhancing their applicability in energy storage and composite materials.
Patent Information
- Application Number
- JP2023184039
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-02-12
- Filing Date
- 2023-10-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2036-09-30
AI Technical Summary
Existing methods for producing graphene often result in materials with finite size and impurities, leading to reduced physical properties and limited applications due to defects and thickness variations.
A method involving electrochemical expansion and subsequent heat treatment of graphite to produce graphene flakes with controlled thickness and low defect density, using a device with a diamond-coated cathode and an anode separated by a separator, applying a voltage to intercalate hydrogen and exfoliate graphene layers.
Produces high-quality graphene flakes with fewer layers, exhibiting graphene-like properties such as high specific surface area and mechanical strength, suitable for applications in batteries, capacitors, and composites.
Smart Images

Figure 0007611988000003 
Figure 0007611988000004 
Figure 0007611988000005
Abstract
Description
[Technical field]
[0001] This application claims priority from German Patent Application No. 102016202202.4, filed with the German Patent and Trademark Office on February 12, 2016, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to graphene and its production, including apparatus and methods for expanding graphite into graphene. [Background technology]
[0003] Ideal graphene is a one-atom-thick layer of graphite with infinite size and no impurities. In reality, graphene is finite in size and contains impurities. Despite these imperfections, the physical properties of real graphene are dominated by an sp2 hybridized carbon atom surrounded by three other carbon atoms arranged in a plane at an angle of 120° from each other, approximating an infinite sheet of pure carbon. Due to this structure, graphene has a number of highly unusual physical properties, including an extremely high elastic modulus-to-weight ratio, high thermal and electrical conductivity, and large, nonlinear diamagnetism. These unusual physical properties allow graphene to be used in a variety of different applications, including conductive coatings, printed electronic components, or conductive inks that can be used to prepare conductive contacts for solar cells, capacitors, batteries, etc.
[0004] Although ideal graphene contains only a single layer of carbon atoms, graphene structures containing multiple carbon layers (e.g., up to 10 layers, or up to 6 layers) can provide comparable physical properties and can be used effectively in many of the various different applications described above. For convenience, both single atomic layer graphene and such multilayer structures having comparable physical properties will be referred to herein as "graphene."
[0005] There are a variety of different types of graphene and other carbonaceous flake materials, the basic characteristics of some of these materials are described below.
[0006] Chemical Vapor Deposition: Chemical vapor deposition (CVD) can be used to produce graphene monolayers with large flake sizes and low defect densities. In some cases, CVD can produce graphene with multiple layers. In some cases, CVD can produce graphene with macroscopic flake sizes (e.g., close to 1 cm in length).
[0007] Examples of the use of CVD for the production of graphene can be found in Non-Patent Documents 1 to 3. According to the abstract of Non-Patent Document 3, "The chemical vapor deposition of graphene on transition metals has been considered a major step towards the commercial realization of graphene. However, transition metal-based fabrication involves an unavoidable transfer step, which can be as complicated as the deposition of graphene itself."
[0008] Natural graphite: Graphite occurs naturally and can be found in crystalline flake-like forms containing tens to thousands of layers. These layers are typically in a regular arrangement, i.e., so-called "AB stacking," with half of the atoms in each layer located exactly above or below the center of the 6-atom ring of the adjacent layer. Because graphite flakes are extremely "thick," they exhibit different physical properties than graphene, many of which are relevant for different applications. For example, graphite flakes are very weak in shear (i.e., the layers can be mechanically separated) and have strong anisotropy in electrical, acoustic, and thermal properties. Due to electrical interactions between neighboring layers, the electrical and thermal conductivity of graphite is lower than that of graphene. As would be expected from a material with a less flat geometry, the specific surface area is also much smaller. Furthermore, at typical flake thicknesses, graphite is not transparent to a variety of different wavelengths of electromagnetic radiation. In some cases, graphite flakes have flake sizes visible to the naked eye (e.g., 1 cm in length).
[0009] Examples of the characterization of graphite-based systems by Raman spectroscopy can be found in [4].
[0010] Graphene oxide: Graphene oxide flakes can be produced using chemical or electrochemical oxidation of graphite to graphite oxide followed by exfoliation. One of the more common approaches was first described by Hummers et al. in 1958 and is commonly referred to as the "Hummers process". 5 In some cases, the graphene oxide can then be partially reduced to remove some of the oxygen.
[0011] However, oxidative etching of graphite not only separates the graphene layers from each other, but also attacks the hexagonal graphene lattice. The resulting graphene oxide is generally highly defective, and as a result, has poor electrical and thermal conductivity, as well as a poor elastic modulus. Furthermore, in-plane etching of graphene flakes typically leads to relatively small lateral dimensions, with flake sizes of less than a few micrometers. In some cases, the average size of graphene oxide flakes in polydisperse samples can be increased using physical methods, such as centrifugation.
[0012] Examples of methods for the production and / or handling of graphene oxide can be found in non-patent literature 6, 7.
[0013] Liquid-phase exfoliation: Flakes of carbonaceous material can be exfoliated from graphite in a suitable chemical environment (e.g., in an organic solvent or in a mixture of water and surfactants). This exfoliation is generally driven by mechanical forces provided, for example, by ultrasound or a blender. Examples of methods for liquid-phase exfoliation can be found in Non-Patent Documents 8, 9.
[0014] Researchers working with liquid-phase exfoliation techniques often refer to the exfoliated carbonaceous flakes as "graphene," but the thickness of most of the flakes produced by such exfoliation techniques often appears to be greater than 10 layers. This can be confirmed, for example, using Raman spectroscopy. -1 The asymmetric shape of the Raman bands around 10 ...
[0015] Exfoliation of expanded graphite: Graphite can be expanded using thermal techniques such as microwave irradiation. Flakes of carbonaceous material can be exfoliated from expanded graphite in a suitable chemical environment (e.g., in an organic solvent or in a mixture of water and surfactants). The exfoliation is generally driven by mechanical forces such as ultrasound or shear forces from a blender. Examples of methods for liquid phase exfoliation of expanded graphite can be found in Non-Patent Document 12 and Patent Document 1.
[0016] Researchers working with exfoliation of expanded graphite often refer to the exfoliated carbonaceous flakes as "graphene," but the thickness of most of these flakes appears to be greater than 10 layers, and even greater than 100 layers. The analytical techniques for determining the thickness of flakes exfoliated from expanded graphite, and the consequences of this thickness, are similar to those described above for liquid phase exfoliation.
[0017] Reduction of graphite: Graphite can be reduced and graphene can be exfoliated in a strongly reducing environment, for example by Birch reduction in lithium. The more graphene is reduced, the more carbon atoms are hydrogenated and sp3 hybridized. In theory, the atomic C / H ratio can approach 1, i.e. the resulting material will be graphane rather than graphene. Examples of methods for the reduction of graphite can be found in Non-Patent Documents 13, 14.
[0018] Lithium and other reducing agents that can be used to reduce graphite are extremely powerful, difficult to handle, and difficult to dispose of.
[0019] Electrochemical expansion: Graphene can also be produced by electrochemical cathodic processing. Examples of methods for electrochemical expansion can be found in US Pat. No. 5,399,413 and US Pat. No. 5,433,133. A reducing environment can also induce hydrogenation of the resulting flakes, as described in US Pat. No. 5,433,133 and US Pat. No. 5,433,133. In general, electrochemical expansion in conventional conditions often fails to produce sufficient quantities of graphene flakes with a thickness of less than 10 layers, which can be confirmed using Raman spectroscopy.
[0020] For validation of the various analytical techniques described herein, various materials were used as references.
[0021] The first such reference material is reduced graphene oxide obtained from Graphenea SA (Avenida Tolosa 76, San Sebastián, Spain, 20018). According to Graphenea SA's product data sheet (available at https: / / cdn.shopify.com / s / files / 1 / 0191 / 2296 / files / Graphenea_rGO_Datasheet_2014‐03‐25.pdf?2923), this sample is 77-87 atomic % carbon, 0-1 atomic % hydrogen, 0-1 atomic % nitrogen, 0 atomic % sulfur, and 13-22 atomic % oxygen. The reduced graphene oxide in this sample is believed to have been produced by a modified Hummers process and subsequent chemical reduction. For convenience, this material will be referred to herein as "Graphenea RGO."
[0022] A second such reference material was obtained from Thomas Swan & Co. Ltd. (Rotary Way, Consett, County Durham, UK DH8 7ND) under the trade name "ELICARB GRAPHENE". A data sheet for this material is available at http: / / www.thomas‐swan.co.uk / advanced‐material / elicarb%C2%AE‐graphene‐products / elicarb%C2%AE‐graphene. According to this data sheet, the graphene in this sample was produced by solvent exfoliation and has a particle size in the range of 0.5–2.0 micrometers. For convenience, this material will be referred to herein as "ELICARB GRAPHENE".
[0023] A third such reference material is expanded graphite (EG), produced by thermal expansion of conventional graphite intercalation compounds typically produced by chemical oxidation. One exemplary expanded graphite is "L2136", a non-commercial material available from Schunk Hoffmann Carbon Technologies AG (Au 62, 4823 Bad Goisern am Hallstättersee, Austria). The company has not disclosed any manufacturing details at this time. For convenience, this material will be referred to herein as "L2136". [Prior art documents] [Patent documents]
[0024] [Patent Document 1] International Publication No. 2015131933 A1 (WO2015131933 A1) [Patent Document 2] International Publication No. 2012120264A1 (WO2012120264 A1) [Patent Document 3] International Publication No. 2015019093 A1 (WO2015019093 A1) [Non-patent literature]
[0025] [Non-Patent Document 1] Science 342: 6159, p. 720‐723 (2013), [Non-Patent Document 2] Science 344: 6181, p. 286-289 (2014), [Non-Patent Document 3] Scientific Reports 3, Art. No. : 2465 (2013) [Non-Patent Document 4] Phys. Chem. Chem. Phys. 9, p. 1276-1290 (2007) [Non-Patent Document 5] J. Am. Chem. Soc. 80 (6) p. 1339‐1339 (1958) [Non-Patent Document 6] Carbon 50(2) p. 470‐475 (2012) [Non-Patent Document 7] Carbon 101 p. 120‐128 (2016) [Non-Patent Document 8] Nature Materials 13 p. 624‐630 (2014) [Non-Patent Document 9] Nature Nanotechnology 3, p. 563‐568 (2008) [Non-Patent Document 10] Phys. Rev. Lett. 2006, 97, 187401 [Non-Patent Document 11] Nat. Mater. 2010, 9, 555‐558 [Non-Patent Document 12] J. Mater. Chem. 22 p. 4806‐4810 (2012) [Non-Patent Document 13] J. Am. Chem. Soc. 134, p. 18689‐18694 (2012) [Non-Patent Document 14] Angew. Chem. Int. Ed. 52, p. 754‐757 (2013) [Non-Patent Document 15] J. Am. Chem. Soc. 133, p. 8888‐8891 (2011) [Non-Patent Document 16] Carbon 83, p. 128‐135 (2015) [Summary of the Invention] [Problems to be Solved by the Invention]
[0026] Described herein are graphene and the production of graphene, including apparatus and methods for expanding graphite into graphene. [Means for solving the problem]
[0027] In a first embodiment, a composition comprises a dehydrogenated graphite consisting of a plurality of flakes, at least one of which has a size greater than 10 square micrometers, an average thickness of 10 atomic layers or less, and a surface area of 1.8 cm when excited at 532 nm. -1 At least 50% of the μ-Raman spectra of dehydrogenated graphite collected at better resolution have defect densities characteristic of D / G area ratios less than 0.5.
[0028] In a second embodiment, a composition comprises dehydrogenated graphite consisting of a plurality of flakes, at least one in ten of which has a size greater than 10 square micrometers and has a diameter of 1.8 cm under excitation at 532 nm. -1 The coefficient of determination values for 2D single peak fitting of μ-Raman spectra of dehydrogenated graphite collected at better resolution are greater than 0.99 for more than 50% of the spectra, and are 1.8 cm for excitation at 532 nm. -1 At least 50% of the μ-Raman spectra of dehydrogenated graphite collected at better resolution have defect densities characteristic of D / G area ratios less than 0.5.
[0029] The first or second aspects above may include one or more of the following features: Greater than 60%, such as greater than 80% or greater than 85% of the μ-Raman spectra of the dehydrogenated graphite may have a coefficient of determination value greater than 0.99. Greater than 40%, such as greater than 50% or greater than 65% of the μ-Raman spectra of the dehydrogenated graphite may have a coefficient of determination value greater than 0.995. At least one in six flakes, such as at least one in four flakes, may have a size greater than 10 square micrometers. At least one in ten flakes, such as at least two in ten flakes, may have a size greater than 25 square micrometers. The average thickness may be 7 atomic layers or less, such as 5 atomic layers or less. The defect density may be characterized by at least 80% of the collected spectra having a D / G area ratio less than 0.5, such as at least 95% of the collected spectra having a D / G area ratio less than 0.5. The defect density may be characterized by at least 80% of the collected spectra having a D / G area ratio less than 0.5, e.g., at least 95% of the collected spectra having a D / G area ratio less than 0.5. The defect density may be characterized by at least 50% of the collected spectra having a D / G area ratio less than 0.2, e.g., at least 70% of the collected spectra having a D / G area ratio less than 0.2. The defect density may be characterized by an average D / G area ratio less than 0.8, e.g., less than 0.5 or less than 0.2. The composition may be a particulate powder of dehydrogenated graphite flakes, e.g., a black particulate powder of dehydrogenated graphite flakes. The flakes of dehydrogenated graphite may be shrunk, crushed, or folded, e.g., to create wrinkles, and the flakes may be assembled into a three-dimensional structure. At 532 nm excitation, the defect density may be 1.8 cm -1 The μ Raman spectrum of dehydrogenated graphite collected at better resolution has a full width at half maximum of the G peak of 20 cm -1 Ultra, for example 25cm -1 Over 30cm -1 It can be more than 1.8 cm when excited at 532 nm.-1 The μ-Raman spectrum of dehydrogenated graphite, collected with better resolution, is at 200 cm -1 Ultra, for example 400cm -1 With a full width at half maximum of more than 1000~1800cm -1 The composition may exhibit a broad peak in the range of 100 to 150 nm. More than 1%, such as more than 5% or more than 10% of the flakes may be thicker than 10 atomic layers. The composition may be, for example, a composite, the composite further comprising activated carbon, or the composite further comprising a polymer. The composition may be a composite, at least 30%, such as at least 50% or at least 70% of the sp3 hybridized carbon sites of the composition are one or more of functionalized with non-hydrogen chemical groups, crosslinked with sp3 hybridized carbon sites of another flake, or otherwise chemically modified.
[0030] The electrode may comprise the composite of the first or second aspect above. The electrode may be part of a battery or an electrochemical capacitor, such as a lithium battery, a lithium ion battery, a silicon anode battery, or a lithium-sulfur battery.
[0031] In a third embodiment, a composition can include hydrogenated graphite consisting of a plurality of flakes, at least one of which has a size greater than 10 square micrometers, an average thickness of 10 atomic layers or less, and a surface area of 1.8 cm when excited at 532 nm. -1 With better resolution and excitation power less than 2 mW, defect densities characteristic of μ-Raman spectra of hydrogenated graphite collected at the focus of a 100× objective lens have average D / G area ratios of 0.2–4, with the majority of defects being reversible hydrogenation of sp3 hybridized carbon sites away from the edges of the flakes.
[0032] In a fourth aspect, a composition can include a reversible hydrogenated graphite consisting of a plurality of flakes, at least one in ten of which has a size greater than 10 square micrometers and has a diameter of 1.8 cm under excitation at 532 nm. -1The coefficient of determination value of the 2D single peak fitting of the μ-Raman spectrum of graphite after heat treatment in an inert atmosphere at 2 mbar and 800° C., collected at better resolution, is greater than 0.99 for more than 50% of the spectra, and is 1.8 cm at excitation of 532 nm. -1 With better resolution and excitation power less than 2 mW, the defect density characteristic of μ-Raman spectra of hydrogenated graphite collected at the focus of a 100× objective lens has an average D / G area ratio of 0.2 to 4. The majority of defects are reversible hydrogenation of sp3 hybridized carbon sites away from the edges of the flakes.
[0033] The third or fourth aspect above may include one or more of the following features: Greater than 60%, such as greater than 80% or greater than 85% of the μ-Raman spectrum of the graphite may have a coefficient of determination value greater than 0.99. Greater than 40%, such as greater than 50% or greater than 65% of the μ-Raman spectrum of the graphite may have a coefficient of determination value greater than 0.995. At least one in six flakes, such as at least one in four flakes, may have a size greater than 10 square micrometers. At least one in ten flakes, such as at least two in ten flakes, may have a size greater than 25 square micrometers. The average thickness may be 7 atomic layers or less, such as 5 atomic layers or less. The defect density may be greater than 1.8 cm at 532 nm excitation. -1At better resolution and with an excitation power of less than 2 mW, at least 50% of the μ-Raman spectra collected at the focus of a 100× objective lens may be characterized as having a D / G area ratio greater than 0.5, such as at least 80% or at least 95% of the collected spectra having a D / G area ratio greater than 0.5. The defect density may be characterized as at least 50% of the collected spectra having a D / G area ratio greater than 0.8, such as at least 60% or at least 90% of the collected spectra having a D / G area ratio greater than 0.8. The defect density may be characterized as having an average D / G area ratio between 0.4 and 2, such as between 0.8 and 1.5. At least 60%, such as at least 75%, of the defects may result in reversible hydrogenation of sp3 hybridized carbon sites away from the edge of the flake. The composition may be a composite, and at least 5%, such as at least 10%, of the sp3 hybridized carbon sites of the composition may be one or more of a) functionalized with a chemical group, b) crosslinked with sp3 hybridized carbon sites of another flake, or c) other chemical modification.
[0034] In a fifth aspect, an apparatus for expanding graphite into graphene comprises at least one container adapted to receive an electrolyte, at least one anode and at least one cathode, said cathode containing or consisting of diamond.
[0035] The fifth aspect may include one or more of the following features. The apparatus may include a separator separating the anode from the cathode. The separator may contact a surface of the anode, or the separator may contain or consist of diamond and / or polytetrafluoroethylene and / or Al2O3 and / or ceramic and / or quartz and / or glass. The apparatus may include a drive means by which the separator and optionally the anode may be rotated. The apparatus may include a separator and optionally an anode displaceably mounted such that the distance between the cathode and the separator may be changed during operation of the apparatus. The apparatus may include a voltage source configured to apply a DC voltage of about 5V to about 60V, or about 15V to about 30V, between the anode and the cathode, the voltage optionally being a pulsed voltage. The apparatus may include a feeder capable of feeding the electrolyte and graphite particles as a dispersion into at least one container, and / or a discharger capable of discharging the electrolyte and graphene flakes as a dispersion from at least one container.
[0036] In a sixth aspect, a method for expanding graphite into graphene comprises introducing graphite particles and at least one electrolyte into at least one container and applying a voltage to at least one anode and at least one cathode to expand the graphite, the cathode containing or consisting of diamond, and hydrogen being produced at the cathode.
[0037] The sixth aspect can include one or more of the following features: Hydrogen can intercalate into and / or chemisorb onto the graphite particles, which exfoliates graphene flakes from the graphite particles. The anode can be separated from the cathode by a separator. The separator can contain or consist of diamond and / or polytetrafluoroethylene and / or Al2O3 and / or ceramic and / or quartz and / or glass. The separator and optionally the anode can be configured to rotate and / or the separator and optionally the anode can be configured to displace, which changes the distance between the cathode and the separator during operation of the device. A voltage of about 5V to about 60V, or a voltage of about 10V to about 50V, or a voltage of about 12V to about 45V, or a voltage of about 15V to about 30V can be applied between the anode and the cathode. Graphite particles can be continuously fed into the container and / or graphene flakes can be continuously removed from the container. The graphene flakes can be dehydrogenated by phototreating, for example, the phototreating can include illuminating the graphene flakes with visible light, UV or microwave, whereby greater than 50% of the hydrogenated sp3 hybridized carbon sites are dehydrogenated. The method can include subsequent heat treatment of the graphene flakes at a temperature of about 100° C. to about 800° C. or about 300° C. to about 650° C. for a period of about 1 minute to about 60 minutes or about 15 minutes to about 40 minutes. The graphene flakes can be sized to be 10 μm or less. 2 Over 50μm 2 Over 100μm 2 The nanoparticles may have an average surface area of greater than or equal to 100 nm.
[0038] The details of one or more embodiments are set forth in the accompanying drawings and the description below. Other features, objects, and advantages will be apparent from the following description and drawings, and from the claims. [Brief description of the drawings]
[0039] [Figure 1] FIG. 1 is a schematic diagram of an apparatus for the expansion of graphite. [Figure 1a]FIG. 1a is a schematic illustration of the hydrogenated graphite and graphene produced by the apparatus of FIG. 1 and the effect of various subsequent processing steps on the materials. [Figure 2-1] 2a and 2b are scanning electron micrographs of graphite after electrochemical expansion. [Figure 2-2] Figure 2c shows a scanning electron micrograph of ELICARB GRAPHENE, and Figure 2d shows a scanning electron micrograph of GRAPHENEA RGO. [Diagram 3] FIG. 3 is a Raman spectrum of expanded and heat-treated graphite particles. [Figure 4] Figure 4a is a spatially resolved μ-Raman microscopy image of a graphene sample produced by the apparatus of Figure 1. Figure 4b is a spatially resolved μ-Raman microscopy image of a GRAPHENEA RGO sample. Figure 4c is a spatially resolved μ-Raman microscopy image of an ELICARB GRAPHENE sample. Figure 4d is a spatially resolved μ-Raman microscopy image of an expanded graphite L2136 sample. [Diagram 5] FIG. 5 is a graph of a pair of overlapping Raman spectra of a single hydrogenated graphite layer. [Figure 6] Figure 6a shows 2D peak spectroscopic data and least square error fitted peaks for graphite suitable for use as a starting material in the apparatus of Figure 1. Figure 6b shows 2D peak spectroscopic data and least square error fitted peaks for ELICARB GRAPHENE. Figure 6c shows 2D peak spectroscopic data and least square error fitted peaks for a first sample of separated dehydrogenated graphite layers. Figure 6d shows 2D peak spectroscopic data and least square error fitted peaks for a second sample of separated dehydrogenated graphite layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] Like reference symbols in the various drawings refer to like elements.
[0041] 1 shows an apparatus 1 that can be used to produce graphene using the methods described herein. The apparatus 1 basically comprises a container 10 bounded by a container wall 101. The container 10 can have a circular base and a generally cylindrical shape.
[0042] In the illustrated embodiment, the cathode 3 is disposed within the container 10 and forms the bottom surface of the container 10 or fills substantially the entire bottom surface of the container. The cathode 3 includes a substrate 31, which may, for example, contain a metal, an alloy, or porous silicon. A diamond layer is deposited on the substrate 31, which may, for example, be formed by chemical vapor deposition. The diamond layer of the cathode 3 may have a thickness of about 0.5 μm to about 20 μm, or about 2 to about 5 μm. The diamond layer of the cathode 3 may optionally be doped with an n- or p-type dopant, which reduces the electrical resistivity of the cathode. In some embodiments, boron may be used as a dopant.
[0043] An anode 4 is also disposed within the container 10. The anode has a shape and size such that it occupies substantially the entire base of the container 10. This creates a roughly homogenous electric field within the container 10, allowing most of the container volume to be utilized for graphene production.
[0044] In some embodiments, the anode 4 may include or be formed of a metal or alloy. In some embodiments, the anode 4 may also include or be formed of diamond. The diamond may be mounted on a substrate as described for the cathode, or may be implemented as a free-standing diamond layer.
[0045] An optional separator 5 is also disposed within the container 10. The separator 5 may include or be formed of, for example, polytetrafluoroethylene (PTFE), diamond, Al2O3, or other materials. The separator 5 may include or be formed of an insulator. The separator 5 may include holes or pores with diameters of less than 10 μm, less than 5 μm, less than 1 micrometer, or less than 0.5 μm. This allows electrolyte (e.g., liquid water) and ions to pass through the separator 5 while preventing the graphite or graphene particles found within the container 10 from contacting the anode 4.
[0046] In the illustrated embodiment, separator 5 separates cathode chamber 30 from anode chamber 40. In other embodiments, separator 5 may be deposited directly on anode 4 or may be secured to anode 4, for example by adhesive bonding. Thus, in some embodiments, anode chamber 40 may be omitted.
[0047] In operation, at least one electrolyte is disposed between the anode 4 and the cathode 3 in the container 10. In some embodiments, the electrolyte may be an aqueous electrolyte, optionally containing substances to increase electrical conductivity, such as, for example, a dilute acid or a salt. In other embodiments, the electrolyte may include or be formed of at least one organic solvent. In yet other embodiments, the electrolyte may include propylene carbonate and / or dimethylformamide and / or organic salts, whose ions are liquid at temperatures below 100° C. due to charge delocalization and steric effects that inhibit the formation of a stable crystal lattice.
[0048] Additionally, graphite 2 in the form of particles is placed in the cathode chamber 30 during operation of the device 1. The graphite particles 2 are dispersed in the electrolyte.
[0049] With this configuration, a voltage of about 5V to about 60V, or about 15V to about 30V, is applied between the cathode 3 and the anode 4 by a voltage source 6. This creates an electric field in the electrolyte.
[0050] The presence of such a high voltage allows the water and / or organic solvents present in the electrolyte to be decomposed with high efficiency. This produces hydrogen at the cathode 3 and oxygen at the anode 4. The graphite placed in the cathode chamber 30 captures this hydrogen by intercalating individual atoms or molecules between the lattice planes of the graphite lattice and / or by chemisorbing individual atoms or molecules on the surface. In other words, the graphite is hydrogenated. The separator 5 now prevents the graphite from coming into contact with the anode 4, for example by penetrating into the anode chamber 40. The graphite placed in the container 10 is thus kept away from the oxygen available at the anode 4, which does not intercalate into the graphite.
[0051] Rotation of the separator 5 within the container 10 can create a shear flow within the cathode chamber 30, which results in mixing of the electrolyte with the dispersed graphite. This mixing can provide uniform distribution of the graphite particles.
[0052] The apparatus 1 may further include an optional feeder 11 capable of introducing the electrolyte and graphite as a dispersion into the cathode chamber 30. The apparatus 1 may further include an optional discharger 12 capable of discharging the hydrogenated graphite 7. Material transfer from the feeder 11, generally concentric with the base of the container 10, to the discharger 12, disposed at the peripheral rim of the container 10, may be driven by rotation of the separator 5. In this manner, the apparatus 1 may be operated continuously by continuously feeding the graphite particles 2 by the feeder 11 and continuously discharging the hydrogenated graphite 7 by the discharger 12.
[0053] FIG. 1a is a schematic illustration of the hydrogenated graphite produced by the apparatus 1, as well as the effect of various subsequent processing steps on said material.
[0054] In particular, reference numeral 105 refers to the hydrogenated graphite suspension discharged from the apparatus 1. As mentioned above, the suspension 105 comprises a hydrogenated graphite layer 106 containing intercalated and / or chemisorbed hydrogen. At least a portion of the chemisorbed hydrogen binds to sp3 hybridized carbon sites 107 away from the edges of the layer 106. In the schematic diagram of Figure 1a, the hydrogenated graphite layer 106 is shown generally as a relatively long curved or straight line, and the sp3 hybridized carbon sites 107 are shown generally as short lines branching off from the relatively long line representing the layer 106.
[0055] The suspension 105 discharged from the device 1 also contains organic solvents or salts 108 from the electrolyte of the electrochemical cell. In the schematic of Figure 1a, the organic solvents or salts 108 are illustrated in the schematic with small "x's."
[0056] The hydrogenated graphite layers 106 are electrochemically expanded relative to the graphite loaded into the device 1. In particular, hydrogenation of the incoming graphite is sufficient to cause at least partial delamination of adjacent layers, which delamination results in "electrochemical expansion" of the graphite without completely physically separating all of the layers from one another. In the schematic of FIG. 1a, electrochemical expansion is illustrated diagrammatically by showing multiple groups of layers 106 in close physical proximity to one another. In some instances, the most adjacent layers 106 include intervening hydrogenation at the sites 107 and / or the organic solvent or salt 108. In other instances, the most adjacent layers 106 do not include intervening hydrogenation at the sites 107 and / or the organic solvent or salt 108.
[0057] Despite the less than ideal finite size of the layers 106, incomplete separation of the layers 106, and the presence of impurities such as sp3 hybridized carbon sites 107, the hydrogenated graphite layers 106 can exhibit graphene-like properties. In particular, the specific surface area and mechanical strength of the hydrogenated graphite layers 106 can be extremely high. The signatures characteristic of AB stacked layers in X-ray or Raman scattering are greatly reduced or absent.
[0058] In some embodiments, organic solvents or salts from the electrolyte can be removed from hydrogenated graphite layer 106 by washing or rinsing with a suitable solvent, such as ethanol or acetone.
[0059] The hydrogenated graphite suspension after washing / rinsing is designated in Figure 1a by reference numeral 110. After washing / rinsing, the number of sp3 hybridized carbon sites 107 in the hydrogenated graphite layer 106 remains essentially unchanged. Thus, in this schematic, layer 106 continues to contain hydrogenated sites 107 in suspension 110.
[0060] Further, while shear forces experienced during cleaning or rinsing, for example, may increase delamination of adjacent layers 106 to some extent, the primary effect of cleaning or rinsing is the removal of organic solvent or salt 108. Thus, in this schematic view, at least some of the layers 106 are shown in close proximity to one another.
[0061] In some embodiments, rather than removing the organic solvent or salt 108 by washing / rinsing, the organic solvent or salt 108 can be removed by selectively evaporating the organic solvent or salt 108 from the suspension 105 in a distillation process. In some embodiments, such a distillation process can be combined with a heat treatment process, described below, to result in suspension 115.
[0062] In some embodiments, both washing / rinsing and distillation processes can be used to remove the organic solvent or salt 108 .
[0063] Regardless of how the suspension 110 is obtained, the hydrogenated graphite layer 106 continues to exhibit graphene-like properties, including high specific surface area and mechanical strength, as well as the absence of signs characteristic of AB stacked layers.
[0064] The suspension 105 or suspension 110 can be treated using a heat treatment process to obtain a dry hydrogenated graphite material 115. This heat treatment process is typically carried out in air or an inert atmosphere below 300° C. The heat treatment process typically involves rapid heating, which transforms the suspension into a gas phase. Since some liquid may also be found between adjacent hydrogenated graphite layers 106, the evaporation of this liquid typically drives the separation of adjacent hydrogenated graphite layers 106, "expanding" the graphite. The material 115 includes hydrogenated graphite layers 106 that include sp3 hybridized carbon sites 107. After the heat treatment, the number of sp3 hybridized carbon sites 107 in the hydrogenated graphite layers 106 typically remains substantially unchanged. Thus, in this schematic, the layers 106 continue to include hydrogenated sites 107 in the hydrogenated graphite material 115.
[0065] Furthermore, although some incidental delamination of adjacent layers 106 may be increased, the primary effect of the heat treatment is the removal of the surrounding organic electrolyte and the expansion of hydrogenated graphite layers 106. Thus, the macroscopic density of hydrogenated graphite layers 106 in material 115 is generally significantly lower than the macroscopic density of hydrogenated graphite layers 106 in suspension 105 or suspension 110.
[0066] After heat treatment, the hydrogenated graphite layers 106 in the dry carbonaceous material 115 continue to exhibit graphene-like properties, including high specific surface area and mechanical strength, as well as the absence of signs characteristic of AB stacked layers.
[0067] In some embodiments, the dried hydrogenated graphite material 115 is subjected to a dehydrogenation heat treatment to obtain a non-separated dried dehydrogenated graphite material 120. This dehydrogenation heat treatment is typically carried out at a temperature above 300° C. to strip hydrogen from the hydrogenated graphite layer 106, resulting in a dehydrogenated graphite layer 116. The dehydrogenated graphite layer 116 is typically 1-10 atomic layers or lattice planes thick and has a low hydrogen content. In some embodiments, the dehydrogenation can be carried out in reduced oxygen partial pressure, for example, 2-20 mbar of nitrogen or argon.
[0068] In this schematic, the dehydrogenated graphite layers 116 are not separated from one another and contain any hydrogenation sites 107. In reality, however, the dehydrogenated graphite layers 116 will generally not be completely hydrogen-free. Rather, the dehydrogenated graphite layers 116 will typically contain some amount of residual hydrogenation sites 107 or other sp3 carbon moieties that are characteristic of the manufacturing process.
[0069] Nevertheless, after the dehydrogenation heat treatment, the dehydrogenated graphite material 120 continues to exhibit not only the graphene-like properties described above (i.e., high specific surface area and mechanical strength, and absence of signs characteristic of AB stacking type layers), but also further graphene-like properties characteristic of sp2 hybridization of substantially all of the carbon in the dehydrogenated graphite layer 116. For example, chemical defects visible by Raman scattering are significantly reduced. Furthermore, the optical transparency decreases, which is associated with a lowering of the band gap. Also, the electronic conductivity of the dehydrogenated graphite layer 116 is higher than that of the layer 106.
[0070] In some embodiments, the unseparated dried hydrogenated graphite material 115 is subjected to a separation process to obtain a separated hydrogenated graphite suspension 125. For example, in some embodiments, the dried hydrogenated graphite material 115 can be dispersed in a suitable liquid, for example with the aid of ultrasound or shear forces, to completely separate the flakes from one another. In some embodiments, water, mesitylene, dimethylsulfoxide, benzene, or mixtures thereof, containing various surfactants, can be used.
[0071] The hydrogenated graphite suspension 125 includes separated hydrogenated graphite layers 106 that include sp3 hybridized carbon sites 107. After separation, the number of sp3 hybridized carbon sites 107 in the hydrogenated graphite layers 106 generally remains substantially unchanged. Thus, in this schematic, the layers 106 continue to include hydrogenated sites 107 in the hydrogenated graphite material 115.
[0072] In this schematic, every single layer 106 is separated from the other layers 106. In reality, however, at least some layers 106 will generally not be separated from all other layers 106. Nevertheless, after the separation process, the layers 106 in the hydrogenated graphite suspension 125 exhibit graphene-like properties, including high specific surface area and mechanical strength, as well as the absence of signs characteristic of AB stacked layers. Moreover, the individual layers 106 are discernible to the naked eye. These layers 106 are often wrinkled and shrunk, indicating that they are only a few atomic layers thick.
[0073] Based on these properties, the hydrogenated graphite suspension 125 is believed to be a useful additive to polymers and other composites. In particular, the hydrogenated graphite suspension 125 provides thin, large flakes that retain some sp3 hybridized carbon. Such sp3 hybridized carbon sites may be useful, for example, as reactive sites for forming chemical bonds or other interactions with other components of the composite.
[0074] In some embodiments, the separated hydrogenated graphite layer 106 in the hydrogenated graphite suspension 125 is subjected to a dehydrogenation heat treatment to obtain the separated dehydrogenated graphite sample 130. For example, the liquid in the graphite suspension 125 can be evaporated (e.g., by drop casting) to provide a dry hydrogenated graphite layer 106. The dry hydrogenated graphite layer 106 can be subjected to a dehydrogenation heat treatment. As another example, the graphite suspension 125 can be confined in a pressure-resistant chamber and the entire suspension 125 can be subjected to a dehydrogenation heat treatment. Thus, the separated dehydrogenated graphite 116 in the graphite sample 130 can be either dry or in a liquid suspension.
[0075] The dehydrogenation heat treatment may involve subjecting the sample to temperatures above 300° C. and low oxygen partial pressures, for example in nitrogen or argon, for example between 2 and 20 mbar.
[0076] In this schematic, the separated dehydrogenated graphite layers 116 in the sample 130 do not contain any hydrogenation sites 107. In reality, however, the separated dehydrogenated graphite layers 116 will generally not be completely hydrogen-free. Rather, the dehydrogenated graphite layers 116 will typically contain some amount of residual hydrogenation sites 107 or other sp3 carbon moieties, which are characteristic of the manufacturing process. Furthermore, in this schematic, every single dehydrogenated graphite layer 116 in the sample 130 is separated from the other layers 116. In reality, however, at least some of the dehydrogenated graphite layers 116 will generally not be separated from all other layers 116. For example, in some embodiments, 1% or more of the layers 116 may have a thickness greater than 10 atomic layers, e.g., greater than 5% or even greater than 10% of the flakes may have a thickness greater than 10 atomic layers. As another example, in some embodiments, 1% or more of the layers 116 may have a thickness greater than 50 atomic layers, or even 100 atomic layers, for example, more than 5% or even 10% of the flakes may have a thickness greater than 50 atomic layers, or even 100 atomic layers.
[0077] Nonetheless, the isolated dehydrogenated graphite layers 116 in sample 130 exhibit graphene-like properties, including high specific surface area and mechanical strength, and the absence of signs characteristic of AB stacked layers, as well as additional graphene-like properties characteristic of sp2 hybridization of nearly all of the carbon in the dehydrogenated graphite layers 116. For example, chemical defects visible by Raman scattering are greatly reduced, optical transparency is reduced, and the electronic conductivity of the graphite layers 116 is high. Furthermore, individual dehydrogenated graphite layers 116 are discernible under a microscope. These graphite layers 116 are often wrinkled and shrunk, indicating that they are only a few atomic layers thick.
[0078] The end result is separated dehydrogenated graphite layers 116, which can be referred to as graphene, in which many of the individual particles are only 1-10 atomic layers thick and have lateral dimensions native to the starting graphite material (often well over 100 micrometers). In contrast to other techniques, this graphene has fewer layers (i.e., smaller thickness) and exhibits graphene-like properties rather than those of bulk graphite. In practice, the method produces graphene with an average area of 10 μm 2 Ultra, 50μm 2 Over 100μm 2 The method and apparatus can produce relatively large graphene flakes, typically greater than 100 nm in diameter. Thus, the method and apparatus can produce high quality graphene in large quantities. The average surface area can be determined by transmission or scanning electron microscopy of a sample containing multiple graphene flakes, and the size of the individual graphene flakes can be determined by image analysis and statistical analysis.
[0079] Additionally, sample 130 of separated dehydrogenated graphite layer 116 can exhibit several characteristics that distinguish sample 130 from graphene and graphite material samples produced by other methods. For example, sample 130 of separated dehydrogenated graphite layer 116 can be produced to provide a fine-grained powder that is black in color and relatively easy to handle in a variety of different contexts. For example, the powder can be mixed in bulk into a liquid with or without a dispersant to form a suspension, such as an ink or a polymer composite.
[0080] Additionally, as noted above, the graphite layers 116 of sample 130 of separated dehydrogenated graphite layers 116 supported by a surface may appear under scanning electron microscopy or other imaging methods due to wrinkling caused by squashing or folding layers 116. Not only does such wrinkling indicate fewer layers and a smaller thickness of layers 116, but the wrinkling also indicates that graphite layers 116 may be capable of fabricating three-dimensional structures that are not limited to a single plane.
[0081] Figures 2a, 2b, 2c and 2d are scanning electron micrographs of different samples at the magnifications indicated by the respective scale bars.
[0082] FIG. 2a is a scanning electron micrograph of an expanded dehydrogenated graphite layer 116 after electrochemical expansion using the method described above, and after simultaneous thermal expansion and dehydrogenation by heating under an argon atmosphere at 2 mbar and 770° C. The graphene can be seen to separate generally vertically along the c-axis into thin layers, with no evidence of in-plane separation or plane breakage. Thus, it is believed that the electrochemical and thermal expansion act specifically to cause c-axis separation, and that the hexagonal crystalline structure and domain size from the source graphite are preserved in the product graphene flakes. These individual layers are similar to the lattice planes of the graphite crystal, i.e., the lateral structure of the graphite used as the starting material is maintained.
[0083] Figures 2b, 2c, and 2d are scanning electron micrographs of samples dip-coated from the dispersion onto a polished boron-doped conductive silicon 100 wafer. In particular, Figure 2b shows graphene layers exfoliated from expanded graphite similar to that shown in Figure 2a, dispersed in a solvent, and dip-coated onto a silicon substrate. The large lateral extent of the graphene is clearly visible, exceeding 100 μm in this particular example.
[0084] In contrast, Figure 2c shows graphene obtained from a commercial ELICARB GRAPHENE dispersion. As shown, the graphene exhibits an average size of about 1 μm, with no flakes greater than 2 micrometers in diameter observed.
[0085] Figure 2d shows commercially available GRAPHENEA RGO dip coated from a dispersion onto a silicon substrate. As shown, the individually identifiable flakes of reduced graphene oxide exhibit diameters of less than 3 micrometers.
[0086] Figure 3 is a Raman spectrum of graphite particles expanded and heat treated as described above with reference to Figure 1 and illustrated in Figure 1a. The symmetry and low full width at half maximum of the 2D band indicates that the graphite has been expanded into graphene flakes less than 10 atomic layers thick. The low relative intensity of the D band confirms the desorption of hydrogen and the low number of structural defects in the graphene flake lattice.
[0087] Figures 4a, 4b, 4c, and 4d are spatially resolved μ-Raman microscopy images of different samples on a substrate. In particular, Figure 4a is an image of a graphene sample produced by electrochemically expanding graphite to graphene using an approach consistent with that described above. Figure 4b is an image of a GRAPHENEA RGO sample. Figure 4c is an image of an ELICARB GRAPHENE sample. Figure 4d is an image of an expanded graphite L2136 sample.
[0088] To make direct comparison of the images meaningful, the handling of the samples in Fig. 4a, 4b, 4c, and 4d prior to imaging was as close to identical as possible. In particular, the four different samples were dispersed in mesitylene and then drop-cast at different locations on a single conductive boron-doped polished Si100 wafer. Prior to drop-casting, the dispersions were placed in weak ultrasound at ~40 W / l to improve homogeneity. Mesitylene evaporated during drop-casting at 300 °C on a hotplate. This would have effectively removed mesitylene from the samples, as the boiling point of mesitylene is approximately 165 °C. To disperse the flakes, deionized water was added to the hot wafer surface and a second wafer was placed on top until all the water had evaporated. Excess material was removed by weak ultrasound treatment in deionized water at ~40 W / l for 3 min. All images were taken from each location on the single wafer.
[0089] To image the four different materials on the sample, a Renishaw InVia μ-Raman spectroscopy system was fitted with a 100x objective lens and set to an excitation wavelength of 532 nm. -1 At least 1.8 cm -1 The Raman shifts at a resolution of 1.0 nm were mapped over dimensions ranging from 20,000 to 40,000 square micrometers with a spatial resolution of 1 + / - 0.1 micrometers.
[0090] The baseline subtracted from the images was determined by fitting the spectrum with a sixth-order polynomial. -1 and 2580~2790cm -1 The Raman shift at 110 cm was excluded from the baseline fitting. The intensity of the G peak is shown in the image. To determine the G peak intensity, a full width at half maximum of 110 cm was used. -1 and assuming that there is a minimum intensity of 0 counts, 1500-1700 cm -1The images were analyzed using ImageJ (https: / / imagej.nih.gov / ij / docs / intro.html) software.
[0091] As shown, images of graphene samples produced by electrochemically expanding graphite into graphene (FIG. 4a) consistently produced flakes having areas greater than 15 square micrometers. In fact, of the flakes analyzed using this approach, at least 10% had areas greater than 15 square micrometers, e.g., at least 15% or at least 20% had areas greater than 15 square micrometers. In some instances, at least 3% had areas greater than 100 square micrometers, e.g., at least 5% or at least 8% had areas greater than 100 square micrometers.
[0092] For flakes having an area greater than 15 micrometers, the average area of the larger flakes was 100-1000 micrometers, e.g., 150-700 micrometers. The size of the flakes appears to roughly follow the dimensions of the graphite used as the starting material and introduced into the apparatus 1 (FIG. 1).
[0093] In contrast, the GRAPHENEA RGO image (FIG. 4b) does not appear to contain any obvious flakes with an area greater than 15 square micrometers. In the histogram of the image spanning 32,500 square micrometers, it contained only one flake with an area greater than 15 square micrometers. However, this single flake could also be an artifact due to incomplete dispersion of the graphene oxide on the substrate. Regardless of whether this single flake is real or an artifact, the average area of this relatively large flake is significantly less than 20 square micrometers.
[0094] The ELICARB GRAPHENE image (Figure 4c) does not show any flakes with an area larger than 15 square micrometers, which is in perfect agreement with the manufacturer's requirement of particle sizes in the 0.5-2.0 micrometer range.
[0095] The image of expanded graphite L2136 (Figure 4d) shows flakes with areas of more than 15 square micrometers. However, microscopy shows that these flakes are thicker than the graphene samples. Using 2D band Raman spectroscopy, the flake thickness, i.e. the average number of continuous AB-stacked graphene layers, can be measured. Details regarding the procedure for evaluating the Raman spectra of the materials in Figures 4a-d to measure the flake thickness are presented below.
[0096] In Raman scattering, an indirect indicator of the number of atomic layers is the symmetry of the 2D band peak. -1 It has been stated that the asymmetric shape of the Raman bands around indicates that the flakes are thicker than 10 atomic layers, and that mechanically exfoliated graphene exhibits asymmetric peak shapes even for flakes with 2 or more atomic layers. Although a direct, statistical determination of the average number of atomic layers is believed to remain elusive, 2D band symmetry is believed to be the most suitable technique for relative comparison of the average number of atomic layers in different samples.
[0097] Peak "symmetry" can be quantified by a variety of different approaches. For example, the coefficient of determination for single-peak pseudo-Voigt peak fitting appears to be a relatively robust approach. For this purpose, a standardized procedure for preparing, fitting and evaluating graphene Raman spectra has been developed and is available at https: / / github.com / graphenestandards / raman. Release v1.0 was used for the following evaluations, and the permalink to the script used is https: / / github.com / graphenestandards / raman / blob / 5cb74ed87545082bd587e4319c061ea2c50e3a6f / DtoG‐2Dsymetry.ipynb. The use of this script allows the evaluation of the recorded Raman data in a clear and uniform manner and allows comparisons between values obtained in different laboratories.
[0098] Raman spectroscopy of graphite and graphene also allows the qualitative identification of structural and chemical defects in the two-dimensional crystals of carbon atoms. Such defects are characterized by the peaks at 1280–1450 cm -1 The so-called “defect” D peak at 1560–1610 cm -1 This can be seen in the "graphite" G peak at position . The G peak arises from in-plane vibrations of sp2 bonded carbon atoms. The D peak arises from out-of-plane vibrations. The underlying Raman scattering event requires defects with momentum conservation and is due to structural and chemical defects. This D peak is not present in the Raman spectrum of defect-free graphite or graphene due to momentum conservation.
[0099] Researchers have attempted to quantitatively determine the defect density from the ratio of the area of the D peak to the area of the G peak, e.g. Nano Lett. 11, p. 3190-3196 (2011) and Spectrosc. Eur. 27, p. 9-12 (2015). The relationship is nonlinear and a maximum is believed to exist for intermediate defect densities. A D / G peak intensity ratio of less than 0.5 together with a single well-defined 2D band is, for example, 1×10 per square centimeter. 11 This is believed to indicate a low defect density of less than one defect. However, this assessment does not take into account effects such as stress (e.g. due to wrinkling).
[0100] Although it is difficult to assign defect densities to an absolute scale (especially for larger flakes with large mechanical deformations), a relative comparison of the D / G area ratios of different materials is straightforward and is considered a good indicator of material properties that depend on said defect ratio, including electrical and thermal conductivity. A standardized procedure for preparing, fitting and evaluating, for example, graphene Raman spectra has been developed and is available at https: / / github.com / graphenestandards / raman. Release v1.0 was used for the following evaluations, and the permalink to the script used is https: / / github.com / graphenestandards / raman / blob / 5cb74ed87545082bd587e4319c061ea2c50e3a6f / DtoG‐2Dsymetry.ipynb. The use of this script allows the evaluation of Raman data in a clean and uniform manner and allows comparisons between values obtained in different laboratories.
[0101] More specifically, the Raman spectrum is -1 and 1.8 cm -1For better spatial resolution, recordings are made with 532 nm laser excitation. The excitation power is set to a value that avoids excessive local heating, e.g. less than 2 mW at the focus of a 100x objective. The spectral range for evaluation of the D and G bands is 1266-1750 cm -1 A second-order polynomial was fitted to the data to obtain the D band at 1280–1450 cm-1 and the D band at 1480–1700 cm-1. -1 The G band was removed and the results were subtracted from the data. Spectra with a signal-to-noise ratio (determined as the squared variance of the data divided by the squared variance of the baseline fitting residuals) less than 5000 were discarded, as such spectra were deemed unable to assess the peaks reliably.
[0102] It is believed that more than 100 spectra must remain to obtain fully meaningful results.
[0103] The first pseudo-Voigt peak for the D band is centered at 1335-1360 cm -1 Limited to 10-160cm -1 The second pseudo-Voigt peak for the G band is fitted by least-squares minimization to the baseline-corrected data with the Gaussian-Lorentzian fraction limited to 0.01–1 and the amplitude limited to positive values. -1 Limited to 10-240cm -1 Fit by least-squares minimization to the baseline-corrected data with the Gaussian-Lorentzian fraction limited to 0.01 to 1 and the amplitude limited to positive values. Divide the area of the first pseudo-Voigt peak obtained by dividing it by the area of the second pseudo-Voigt peak, and the result is the respective D / G area ratio.
[0104] This procedure yields a value for the D / G area ratio, where, for example, values less than 0.8, less than 0.5, or less than 0.2 are indicative of moderate, low, or very low defect density, respectively.
[0105] The spatially resolved Raman measurements shown in Figure 4 were evaluated according to the procedure described above. The results in terms of the D / G area ratio are shown in Table 1.
[0106] [Table 1]
[0107] Material produced by electrochemical expansion and separation of individual flakes, corresponding to hydrogenated graphite layer 106 drop cast from suspension 125 of FIG. 1a and dried at 300° C., exhibited relatively high D / G area ratios, with less than 12% exhibiting a D / G area ratio below 0.8, with an average value of 1.1±0.2. Thus, the average D / G area ratio of hydrogenated graphite layer 106 from suspension 125 may be lower than that of GRAPHENEA RGO, which has an average D / G area ratio of 1.3±0.1. Both of these average D / G area ratios are significantly higher than the values for expanded graphite L2136, which has an average D / G area ratio of 0.07±0.07.
[0108] These results are believed to indicate that the hydrogenated graphite layers 106 and GRAPHENEA RGO drop cast from suspension 125 and dried at 300° C. have structural or chemical defect densities higher than the defect density of graphite L2136 and the defect density of dehydrogenated graphite layers 116. For example, the defect densities of the flakes 106 and GRAPHENEA RGO in suspension 125 are greater than 1×10 per square centimeter. 11 defects, or for example 1×10 per square centimeter 14 This is considered to be higher than individual defects (Spectrosc. Eur. 2015, 27, 9-12).
[0109] The hydrogenated graphite layer 106 from the suspension 125 can be converted to a dehydrogenated graphite layer 116 by drop casting the hydrogenated graphite layer 106 onto a wafer and heat treating the wafer at 800° C. for 30 minutes under a nitrogen atmosphere of 2 mbar. After this heat treatment, a D / G area ratio of 0.17±0.06 can be measured at a single point. This indicates that more than 50% of the defects in the hydrogenated graphite layer 106 before thermal dehydrogenation were chemical defects related to hydrogen chemisorption. Hydrogen chemisorption is known to be reversible (Science 2009, 323, 610-613). In contrast, graphene oxide generally does not exhibit a D / G area ratio below 0.5, even after thermal reduction at comparable temperatures (Adv. Mater. 2013, 25, 3583-3587). This is consistent with the D / G area ratio measured for GRAPHENEA RGO, which is a reduced graphene oxide that still results in a D / G area ratio greater than 1.
[0110] On the other hand, these results indicate that the defect density in the dehydrogenated graphite layer 116 is 1×10 per square centimeter. 11 Fewer than 5x10 defects per square centimeter, e.g. 10 Fewer than 10 defects or 3 x 10 defects per square centimeter 10 This is believed to indicate that there are fewer than 1 defect.
[0111] Moreover, despite the extremely low defect density, some dehydrogenated graphite layers 116 retain features that may be indicative of remaining defects. For example, in some embodiments, the defect density is 1.8 cm at 532 nm excitation. -1 The full width at half maximum of the G peak in a μ-Raman spectrum collected at better resolution is 20 cm -1 Ultra, for example 25cm -1 Over 30cm -1 As another example, in some embodiments, the optical density is greater than 1.8 cm when excited at 532 nm. -1The μ-Raman spectrum of dehydrogenated graphite, collected with better resolution, is at 200 cm -1 Ultra, for example 400cm -1 With a full width at half maximum of more than 1000~1800cm -1 It shows a broad peak in the range.
[0112] In summary, heat treatment of a hydrogenated graphite layer, such as hydrogenated graphite layer 106, at temperatures above 300° C. can result in a significant reduction in the Raman D / G area ratio by a factor of two or more. The reduction in the Raman D / G area ratio is believed to be due to dehydrogenation. The reduction in the Raman D / G area ratio can be by a factor of four or more, such as a factor of six or more. The reduction in the Raman D / G area ratio is believed to be indicative of the production of graphene with a low defect density. For example, in some embodiments, more than 50% of the statistical spectra exhibit a D / G area ratio of less than 0.8, such as more than 90% exhibiting a D / G area ratio of less than 0.8. In some embodiments, more than 50% (e.g., more than 90%) exhibit a D / G area ratio of less than 0.5. In some embodiments, more than 20% (e.g., more than 50%) exhibit a D / G area ratio of less than 0.2. The average D / G area ratio of at least 100 statistical spectra evaluated by the procedure described above is less than 0.8, such as less than 0.5 or less than 0.2.
[0113] Along with investigating the defect density, Raman scattering in graphene also provides an indirect indication of the number of atomic layers using the peak symmetry of the 2D band. -1 It has been stated that the asymmetric shape of the Raman bands around 10 indicates that the flakes are thicker than 10 atomic layers, and that mechanically exfoliated graphene exhibits asymmetric peak shapes even for flakes with 2 or more atomic layers. Although a direct statistical determination of the average number of atomic layers is believed to remain elusive, 2D band symmetry is believed to be the most suitable technique for relative comparison of the average number of atomic layers in different samples.
[0114] Peak "symmetry" can be quantified by a variety of different approaches. For example, the coefficient of determination for single-peak pseudo-Voigt peak fitting appears to be a relatively robust approach. For this purpose, a standardized procedure for preparing, fitting and evaluating graphene Raman spectra has been developed and is available at https: / / github.com / graphenestandards / raman. Release v1.0 was used for the following evaluations, and the permalink to the script used is https: / / github.com / graphenestandards / raman / blob / 5cb74ed87545082bd587e4319c061ea2c50e3a6f / DtoG‐2Dsymetry.ipynb. The use of this script allows the evaluation of the recorded Raman data in a clear and uniform manner and allows comparisons between values obtained in different laboratories.
[0115] More specifically, the Raman spectrum is -1 and 1.8 cm -1 For better spatial resolution, the recordings are made using a 532 nm laser excitation. The spectral range for the evaluation of the 2D bands is 2555-2810 cm -1 A linear baseline is subtracted by fitting a straight line to the data, while the peaks are cut between 2600 and 2790 cm -1 Remove the 2D bands from the data set. Subtract the result from the data. Discard spectra with a signal-to-noise ratio (determined as the squared variance of the data divided by the squared variance of the baseline fitting residuals) below 5000, since it is believed that such spectra do not allow reliable assessment of peak shape. It is believed that more than 100 spectra must remain to obtain fully meaningful results. The pseudo-Voigt peak is identified as having a peak centered between 2650 and 2750 cm. -1 Limited to 10-240cm -1Fit by least-squares minimization to baseline-corrected data with bounds of 0.01 to 1, Gaussian-Lorentzian fractions limited to 0.01 to 1, and amplitudes limited to positive values. To limit the effects of detector noise, a window of 5 data points after fitting is fitted between 2600 and 2790 cm. -1 The fit residuals and Raman intensity data are smoothed by calculating a moving average of the data in. A decision function is calculated from the result as 1 minus the variance of the smoothed residuals divided by the variance of the smoothed Raman intensity data.
[0116] This procedure allows the determination of the coefficient of determination for 2D single peak fitting (2DR), which is considered to be a measure of the symmetry of the 2D Raman bands of graphite and graphene. 2 ) is obtained. Values close to 1 are considered to indicate high symmetry of the 2D bands, while smaller values are considered to indicate increased asymmetry of the 2D bands.
[0117] If the D / G area ratio of the evaluated graphite or graphene is less than 0.5, the symmetry of the 2D band is considered to be an indication of the average thickness of the flake. In this regard, materials containing many defects often show asymmetry of the 2D peak for very thin layers, even for a single layer. On the other hand, the obvious asymmetry of relatively thick layers is screened by the very broad width of the 2D peak, which is typical for materials with a high D / G area ratio. For these reasons, the 2D band symmetry evaluation of the flake thickness was only applied to materials that fulfilled the criterion of a D / G area ratio less than 0.5. A high symmetry is considered to be an indication of a relatively low number of AB stacked layers, for example less than 10 layers, for example less than 5 layers, or even a single layer. An increase in the number of layers increases the coefficient of determination (2DR) of the 2D single peak fitting. 2 ) corresponds to a decrease in the value of
[0118] After dehydrogenation, the D / G area ratio is less than 0.5, allowing evaluation of the 2D peak symmetry. The Raman spectrum of the same spot shown in Figure 4a (i.e. after heat treatment at 800 °C for 30 min in N2 at 2 mbar) is measured and the coefficient of determination is derived using the procedure described above. The results are shown in Table 2.
[0119] [Table 2]
[0120] For the isolated dehydrogenated graphite layer 116, more than 80% of the spectra had an R better than 0.99. 2 The expanded graphite L2136 flakes showed a R 2 No spectra showed a better than 0.99.
[0121] To help ensure that the individual flake samples were representative of the original composition of the material, an additional procedure was used: A viscous suspension of the flakes in mesitylene was prepared. This suspension was spread onto a glass carrier to obtain samples of at least 1 × 1 mm. 2 The resulting black film was of many overlapping particles with an area of 100 nm. This area was sufficiently smooth to allow μ-Raman spectroscopy. The Raman spectrum was recorded from 1260 to 2810 cm -1 and 1.8 cm -1 For better spatial resolution, recordings were made with 532 nm laser excitation. The excitation power was set to a value that avoided excessive local heating, e.g., less than 5 mW at the focus of a 100x objective. 2 121 spectra were recorded at 0.1 mm intervals over an area of 121 mm. 2 The values are described above and shown in Table 2. For the isolated dehydrogenated graphite layer 116 (800° C., 2 mbar, 30 min), more than 50% of the spectra had an R of more than 0.99. 2 For example, more than 60%, more than 80%, or more than 85% have an R of more than 0.99. 2In fact, for the isolated dehydrogenated graphite layer 116 (800° C., 2 mbar, 30 min), more than 40% of the spectra had an R of more than 0.995. 2 For example, more than 50% or more than 65% of the R 2 showed.
[0122] For the source graphite material (e.g., the graphite introduced into the apparatus 1), more than 90% of the spectra have an R of less than 0.98. 2 with an R of over 0.99 2 More than 40% of the spectra obtained from ELICARB GRAPHENE had an R better than 0.99. 2 showed an R value better than 0.995. 2 More than 10%, such as more than 40% or such as more than 60% of the spectra from both the unseparated and separated dehydrogenated graphite layers 116 had an R better than 0.995. 2 had the following characteristics:
[0123] Although the relationship between the 2D peak symmetry and the average thickness of the AB-stacked layers in the flakes is currently only qualitative, many researchers believe that the asymmetry of the 2D peak is due to more than one atomic layer of AB-stacked graphite, for example more than 11 atomic layers of AB-stacked graphite. Turbostratic stacking, which is stacking of flakes in a random orientation, does not seem to result in peak asymmetry, but does seem to result in a broadening of the 2D peak. Thus, it may not be possible to distinguish between single atomic layer flakes and flakes with more than one atomic layer, for example more than 11 atomic layers, if the stacking of the latter layers is turbostratic.
[0124] Many researchers also believe that 10 or more AB stacked layers result in a clear asymmetry of the 2D bands in Raman spectroscopy. Figure 6 shows exemplary 2D peak spectra of various samples. In particular, Figure 6a shows spectroscopic data 605 and least square error fitting peaks 610 of graphite suitable for use as a starting material in the apparatus 1. Figure 6b shows spectroscopic data 615 and least square error fitting peaks 620 of ELICARB GRAPHENE. Figure 6c shows spectroscopic data 625 and least square error fitting peaks 630 for a first sample of separated dehydrogenated graphite layer 116. Figure 6d shows spectroscopic data 635 and least square error fitting peaks 640 for a second sample of separated dehydrogenated graphite layer 116.
[0125] These images have R of 0.98, 0.99, and 0.995. 2 It has been shown that the threshold value can distinguish peaks with different symmetries. Based on these results, the inventors estimate that more than 50% of the graphene produced by electrochemical expansion and subsequent heat treatment has less than 10 AB stacked atomic layers, such as more than 60% or more than 70% has less than 10 AB stacked atomic layers. Furthermore, the inventors estimate that more than 10%, such as more than 20% or more than 50% of the graphene produced by electrochemical expansion and subsequent heat treatment is single layer graphene.
[0126] In contrast, the inventors estimate that greater than 90% of source graphite material suitable for introduction into apparatus 1 has 10 or more AB stacked layers. The inventors also estimate that greater than 90%, such as greater than 95% or greater than 99%, of conventional expanded graphite has greater than 10 AB stacked layers.
[0127] The hydrogenated and dehydrogenated graphitic materials described herein can be used in semiconductor devices (e.g., in transistors). The graphitic materials can also be used in display screens, such as touch screens, solar cells, and nanotechnology devices. The graphitic materials can also be used as component electrodes in supercapacitors and batteries, such as lithium, lithium compound, and non-lithium batteries. The graphitic materials can also be used as conductive layers, such as conductive transparent layers. The graphitic materials can also be used in inks and paints, including functional inks and paints. The graphitic materials can also be used in composites, such as with polymers or metals, including for use as thermal interface materials or electromagnetic barriers.
[0128] A number of embodiments have been described. Nevertheless, it will be appreciated that various modifications may be made. For example, a variety of different solvents and dispersants can be used. Polydisperse heterogeneous graphene samples can be treated to reduce polydispersity and / or improve homogeneity. The size distribution can be adjusted, for example, by filtration or centrifugation. The amount of hydrogenation can be adjusted by the electrochemical reaction conditions, for example by adjusting the voltage and amount of water used. The layer number distribution can be changed by sedimentation, centrifugation or other techniques.
[0129] As another example, the hydrogenated graphite layer can be dehydrogenated by phototreatment. For example, visible light, UV, and microwave can all be used to drive the dehydrogenation of the hydrogenated graphite layer, thus reducing the D / G area ratio, which is believed to correspond to a reduction in defect density. FIG. 5 is a graph of a pair of overlapping Raman spectra of a single spot of hydrogenated graphite layer 106 after drop casting from suspension 125 and drying at 300° C. In particular, spectrum 505 was collected before and spectrum 510 was collected after laser irradiation at around 25 mW at the focus of a 100× objective lens for several seconds under ambient conditions. As shown, the D / G area ratio has decreased by more than 5 times, indicating that hydrogenated graphite layer 106 has been converted to dehydrogenated graphite layer 116.
[0130] Accordingly, other embodiments are within the scope of the following claims.
[0131] [Additional note 1] 1. A composition comprising a plurality of flakes of dehydrogenated graphite, The flakes include: At least one in ten has a size greater than 10 square micrometers; The average thickness is 10 atomic layers or less; 1.8 cm at 532 nm excitation -1 wherein at least 50% of μ Raman spectra of said dehydrogenated graphite collected at better resolution have defect densities characteristic of a D / G area ratio of less than 0.5.
[0132] [Additional note 2] 1. A composition comprising a plurality of flakes of dehydrogenated graphite, The flakes include: At least one in ten has a size greater than 10 square micrometers; 1.8 cm at 532 nm excitation -1the coefficient of determination value of a 2D single peak fit of μ Raman spectra of said dehydrogenated graphite collected at better resolution is greater than 0.99 for more than 50% of said spectra; 1.8 cm at 532 nm excitation -1 wherein at least 50% of μ Raman spectra of said dehydrogenated graphite collected at better resolution have defect densities characteristic of a D / G area ratio of less than 0.5.
[0133] [Additional note 3] 3. The composition of claim 1 or 2, wherein more than 60%, such as more than 80% or more than 85% of the μ Raman spectra of the dehydrogenated graphite have a coefficient of determination value of greater than 0.99.
[0134] [Additional note 4] 4. The composition of any one of claims 1 to 3, wherein more than 40%, such as more than 50% or more than 65% of the μ Raman spectra of the dehydrogenated graphite have a coefficient of determination value greater than 0.995.
[0135] [Additional note 5] 5. The composition of any one of claims 1 to 4, wherein at least one of six of the flakes, such as at least one of four of the flakes, has a size greater than 10 square micrometers.
[0136] [Additional note 6] 6. The composition of any one of claims 1 to 5, wherein at least one of ten flakes, such as at least two of ten flakes, have a size greater than 25 square micrometers.
[0137] [Additional note 7] 7. The composition according to any one of claims 1 to 6, wherein the average thickness is 7 atomic layers or less, for example 5 atomic layers or less.
[0138] [Additional note 8] The composition according to any one of appended claims 1 to 7, wherein the defect density is characterized in that at least 80% of the collected spectra have a D / G area ratio less than 0.5, such as at least 95% of the collected spectra have a D / G area ratio less than 0.5.
[0139] [Additional note 9] The composition of any one of appended claims 1 to 8, wherein the defect density is characterized in that at least 80% of the collected spectra have a D / G area ratio of less than 0.5, such as at least 95% of the collected spectra have a D / G area ratio of less than 0.5.
[0140] [Additional Note 10] The composition of any one of appended claims 1 to 9, wherein the defect density is characterized in that at least 50% of the collected spectra have a D / G area ratio of less than 0.2, such as at least 70% of the collected spectra have a D / G area ratio of less than 0.2.
[0141] [Additional Note 11] 11. The composition according to any one of claims 1 to 10, wherein the defect density is an average D / G area ratio of less than 0.8, for example less than 0.5 or less than 0.2.
[0142] [Additional Note 12] 12. The composition according to any one of appended items 1 to 11, wherein the composition is a fine particle powder of dehydrogenated graphite flakes, for example a black fine particle powder of dehydrogenated graphite flakes.
[0143] [Additional Note 13] the plurality of flakes of dehydrogenated graphite are shrunk, crushed, or folded, e.g., to create wrinkles; 13. The composition of any one of claims 1 to 12, wherein the plurality of flakes are assembled into a three-dimensional structure.
[0144] [Additional Note 14] 1.8 cm at 532 nm excitation-1 The μ Raman spectrum of the dehydrogenated graphite collected at better resolution has a full width at half maximum of the G peak of 20 cm -1 Ultra, for example 25cm -1 Over 30cm -1 The composition according to any one of claims 1 to 13, wherein the molecular weight of the composition is greater than or equal to 1.
[0145] [Additional Note 15] 1.8 cm at 532 nm excitation -1 The μ Raman spectrum of the dehydrogenated graphite collected at better resolution is -1 Ultra, for example 400cm -1 With a full width at half maximum of more than 1000~1800cm -1 The composition according to any one of appended items 1 to 14, which exhibits a broad peak in the range of
[0146] [Additional Note 16] 16. The composition of any one of clauses 1 to 15, wherein more than 1% of the flakes, such as more than 5% or more than 10%, are more than 10 atomic layers thick.
[0147] [Additional Note 17] The composition is, for example, a complex, 17. The composition according to any one of claims 1 to 16, wherein the complex further comprises activated carbon, or the complex further comprises a polymer.
[0148] [Additional Note 18] the composition is a complex, The sp of the composition 3 At least 30%, such as at least 50% or at least 70% of the hybridized carbon sites are: a) functionalization with non-hydrogen chemical groups; b) Another flake sp 3 Crosslinking with hybridized carbon moieties; or c) Other chemical modifications The composition according to any one of claims 1 to 17, wherein the composition is subjected to one or more of the following:
[0149] [Additional Note 19] An electrode comprising the composition according to any one of claims 1 to 18.
[0150] [Additional Note 20] A battery or an electrochemical capacitor comprising the electrode according to claim 19, The battery is a battery or an electrochemical capacitor, for example a lithium battery, a lithium ion battery, a silicon anode battery, or a lithium-sulfur battery.
[0151] [Additional Note 21] 1. A composition comprising hydrogenated graphite consisting of a plurality of flakes, The flakes include: At least one in ten has a size greater than 10 square micrometers; The average thickness is 10 atomic layers or less; 1.8 cm at 532 nm excitation -1 The defect density characteristic of μ-Raman spectra of the hydrogenated graphite collected at the focus of a 100× objective with better resolution and excitation power less than 2 mW, has an average D / G area ratio of 0.2-4, with the majority of defects located at sp 3 The composition, wherein the hybridized carbon site is a reversible hydrogenation.
[0152] [Additional Note 22] 1. A composition comprising a reversible hydrogenated graphite comprising a plurality of flakes, The flakes include: At least one in ten has a size greater than 10 square micrometers; 1.8 cm at 532 nm excitation -1 the coefficient of determination value of a 2D single peak fit of μ-Raman spectra of said graphite after heat treatment in an inert atmosphere at 2 mbar and 800° C. collected at better resolution is greater than 0.99 for more than 50% of said spectra; 1.8 cm at 532 nm excitation -1The defect density characteristic of μ-Raman spectra of the hydrogenated graphite collected at the focus of a 100× objective with better resolution and excitation power less than 2 mW, has an average D / G area ratio of 0.2-4, with the majority of defects located at sp 3 The composition, wherein the hybridized carbon site is a reversible hydrogenation.
[0153] [Additional note 23] 23. The composition of claim 21 or 22, wherein more than 60%, such as more than 80% or more than 85% of the μ Raman spectra of the graphite have a coefficient of determination value of more than 0.99.
[0154] [Additional note 24] 24. The composition of any one of claims 21 to 23, wherein more than 40%, such as more than 50% or more than 65% of the μ Raman spectra of the graphite have a coefficient of determination value greater than 0.995.
[0155] [Additional note 25] 25. The composition of any one of claims 21 to 24, wherein at least one of six of the flakes, such as at least one of four of the flakes, has a size greater than 10 square micrometers.
[0156] [Additional note 26] 26. The composition of any one of claims 21 to 25, wherein at least one of ten flakes, such as at least two of ten flakes, have a size greater than 25 square micrometers.
[0157] [Additional note 27] 27. The composition according to any one of claims 21 to 26, wherein the average thickness is 7 atomic layers or less, for example 5 atomic layers or less.
[0158] [Additional note 28] The defect density is 1.8 cm under excitation at 532 nm. -128. The composition according to any one of claims 21 to 27, characterized in that at least 50% of the μ Raman spectra collected at the focus of a 100x objective with better resolution and an excitation power of less than 2 mW have a D / G area ratio of greater than 0.5, such as at least 80% or at least 95% of the collected spectra having a D / G area ratio of greater than 0.5.
[0159] [Additional note 29] 29. The composition of any one of claims 21 to 28, wherein the defect density is characterized in that at least 50% of the collected spectra have a D / G area ratio greater than 0.8, such as at least 60% or at least 90% of the collected spectra have a D / G area ratio greater than 0.8.
[0160] [Additional note 30] 30. The composition according to any one of appended items 21 to 29, wherein the defect density is an average D / G area ratio of 0.4 to 2, for example 0.8 to 1.5.
[0161] [Additional note 31] At least 60%, for example at least 75%, of the defects are sp 3 The composition according to any one of items 21 to 30, which is a reversible hydrogenation of a hybrid carbon moiety.
[0162] [Additional note 32] the composition is a complex, The sp of the composition 3 At least 5%, such as at least 10%, of the hybridized carbon sites are: a) functionalization with non-hydrogen chemical groups; b) Another flake sp 3 Crosslinking with hybridized carbon moieties; or c) Other chemical modifications The composition according to any one of claims 21 to 31, which is subjected to one or more of the following:
[0163] [Additional note 33] A device (1) for expanding graphite (2) into graphene (7), comprising at least one container (10) adapted to receive an electrolyte, at least one anode (4) and at least one cathode (3), The cathode (3) is characterized in that it contains diamond or is made of diamond. A device that is characteristic of something.
[0164] [Additional note 34] Further comprising a separator (5) separating the anode (4) from the cathode (3), 34. The device according to claim 33.
[0165] [Additional note 35] the separator (5) contacts the surface of the anode (4); or The separator (5) contains or consists of diamond and / or polytetrafluoroethylene and / or Al2O3 and / or ceramic and / or quartz and / or glass. 35. The device according to claim 33 or 34,
[0166] [Additional note 36] 36. The apparatus according to any one of claims 33 to 35, further comprising a drive means by which the separator (5) and optionally the anode (4) can be rotated.
[0167] [Additional note 37] 37. The device according to any one of claims 33 to 36, characterized in that the separator (5) and optionally the anode (4) are displaceably mounted so that the distance between the cathode (3) and the separator (5) can be changed during operation of the device (1).
[0168] [Additional note 38] a voltage supply configured to apply a DC voltage between the anode and the cathode of about 5 V to about 60 V, or about 15 V to about 30 V; 38. The apparatus according to any one of claims 33 to 37, wherein the voltage is optionally a pulsed voltage.
[0169] [Additional note 39] and / or further comprising a supply device (11) capable of supplying the electrolyte and graphite particles (2) as a dispersion to said at least one container (10); 39. The apparatus according to any one of claims 33 to 38, further comprising a discharge device (12) capable of discharging the electrolyte and graphene flakes (7) from the at least one container (10) as a dispersion.
[0170] [Additional note 40] A method for expanding graphite (2) into graphene (7), comprising the steps of: Introducing graphite particles (2) and at least one electrolyte into at least one container (10), The method comprises applying a voltage (6) to at least one anode (4) and at least one cathode (3) to expand the graphite (2), The cathode (3) contains or consists of diamond, Hydrogen is produced at the cathode. A method comprising:
[0171] [Additional note 41] 41. The method of claim 40, wherein the hydrogen is intercalated in and / or chemisorbed onto the graphite particles (2), thereby exfoliating graphene flakes (7) from the graphite particles (2).
[0172] [Additional note 42] 42. The method according to claim 40 or 41, characterized in that the anode (4) is separated from the cathode (3) by a separator (5).
[0173] [Additional note 43] 43. The method according to claim 42, wherein the separator (5) contains or consists of diamond and / or polytetrafluoroethylene and / or Al2O3 and / or ceramic and / or quartz and / or glass.
[0174] [Additional note 44] the separator (5) and optionally the anode (4) are arranged to rotate; and / or The separator (5) and optionally the anode (4) are configured to be displaced, whereby the distance between the cathode (3) and the separator (5) changes during operation of the device (1). 44. The method according to any one of claims 40 to 43,
[0175] [Additional note 45] The method according to any one of appended items 40 to 44, wherein the voltage is about 5 V to about 60 V, or about 10 V to about 50 V, or about 12 V to about 45 V, or about 15 V to about 30 V, applied between the anode (4) and the cathode (3).
[0176] [Additional note 46] the graphite particles (2) are continuously fed into the container (10); and / or The graphene flakes (7) are continuously removed from the container (10). 46. The method according to any one of claims 40 to 45,
[0177] [Additional note 47] The method further comprises a step of dehydrogenating the graphene flakes (7) by light treatment, For example, the light treatment may further comprise illuminating the graphene flakes (7) with visible light, UV or microwaves, Hydrogenation sp 3 47. The method according to any one of claims 40 to 46, wherein more than 50% of the hybridized carbon sites are dehydrogenated.
[0178] [Additional note 48] 48. The method according to any one of appended items 40 to 47, further comprising a step of subsequent heat treatment of the graphene flakes (7) at a temperature of about 100° C. to about 800° C., or about 300° C. to about 650° C., for a period of about 1 minute to about 60 minutes, or about 15 minutes to about 40 minutes.
[0179] [Additional note 49] The graphene flakes (7) are 10 μm 2 Over 50μm 2 Over 100μm 2 49. The method according to any one of appended items 40 to 48, wherein the nanoparticles have an average surface area of greater than 100 nm.
Claims
1. 1. An apparatus for expanding graphite into graphene, comprising: a container in which graphite particles and an electrolyte are introduced; a cathode disposed within the container; an anode disposed within the container; a separator separating the cathode and the anode within the container; a voltage supply configured to apply a DC voltage between the anode and the cathode of between 5V and 60V, the DC voltage being any pulsed voltage; Equipped with by applying the DC voltage to the anode and the cathode, hydrogen is generated at the cathode, and the generated hydrogen is intercalated between lattice planes of the graphite particles and / or chemisorbed on the surfaces of the graphite particles, thereby exfoliating graphene flakes from the graphite particles. The apparatus.
2. The anode contains diamond.
2. The apparatus of claim 1.
3. the voltage supply is configured to apply the DC voltage between the anode and the cathode of between 15V and 30V; 3. Apparatus according to claim 1 or 2.
4. the separator contacts a surface of the anode; An apparatus according to any one of claims 1 to 3.
5. The separator is made of diamond and / or polytetrafluoroethylene and / or Al. 2 O 3 and / or ceramic and / or quartz and / or glass, An apparatus according to any one of claims 1 to 4.
6. Further comprising a drive means, The drive means can be used to rotate the separator and the anode. An apparatus according to any one of claims 1 to 5.
7. the separator and the anode are displaceably mounted so that the distance between the cathode and the separator can be changed during operation of the device; An apparatus according to any one of claims 1 to 6.
8. a supply device capable of supplying the electrolyte and graphite particles as a dispersion to the container; An apparatus according to any one of claims 1 to 7.
9. and a discharge device capable of discharging the electrolyte and graphene flakes from the container as a dispersion. An apparatus according to any one of claims 1 to 8.
10. 1. A method for expanding graphite to graphene, comprising: Introducing graphite particles and an electrolyte into the container; The method of expanding the graphite by applying a voltage to an anode and a cathode, Hydrogen is produced at the cathode; the hydrogen is intercalated into and / or chemisorbed onto the graphite particles, thereby exfoliating graphene flakes from the graphite particles; The method.
11. The anode contains diamond. The method of claim 10.
12. the anode is separated from the cathode by a separator; 12. The method according to claim 10 or 11.
13. The separator is made of diamond and / or polytetrafluoroethylene and / or Al. 2 O 3 and / or ceramic and / or quartz and / or glass, The method of claim 12.
14. The separator and the anode may be configured to rotate.
14. The method according to claim 12 or 13.
15. displacing the separator and the anode, thereby changing the distance between the cathode and the separator during operation. The method according to any one of claims 12 to 14.
16. the voltage of 5V to 60V is applied between the anode and the cathode; The method according to any one of claims 10 to 15.
17. the voltage of 10V to 50V is applied between the anode and the cathode; The method according to any one of claims 10 to 15.
18. the voltage of 12V to 45V is applied between the anode and the cathode; The method according to any one of claims 10 to 15.
19. the voltage of 15V to 30V is applied between the anode and the cathode; The method according to any one of claims 10 to 15.
20. continuously feeding the graphite particles into the container. The method according to any one of claims 10 to 19.
21. continuously removing the graphene flakes from the container. The method according to any one of claims 10 to 20.
22. The method further comprises the step of phototreating the graphene flakes to dehydrogenate them, For example, the light treatment may further include illuminating the graphene flakes with visible light, UV, or microwaves; Hydrogenation sp 3 More than 50% of the hybridized carbon sites are dehydrogenated; The method according to any one of claims 10 to 21.
23. further comprising a step of subsequent heat treatment of the graphene flakes at a temperature between 100° C. and 800° C. for a period between 1 minute and 60 minutes. The method according to any one of claims 10 to 22.
24. In the subsequent heat treatment step, the treatment is carried out at a temperature between 300° C. and 650° C.; 24. The method of claim 23.
25. In the subsequent heat treatment step, the treatment is carried out for a period of 15 minutes to 40 minutes.
25. The method of claim 23 or 24.
26. The graphene flakes are 10 μm 2 having an average surface area of greater than The method according to any one of claims 10 to 25.
27. The graphene flakes are 50 μm 2 having an average surface area of greater than The method according to any one of claims 10 to 25.
28. The graphene flakes are 100 μm 2 having an average surface area of greater than The method according to any one of claims 10 to 25.
Citation Information
Patent Citations
Method for preparing graphene by electrochemical swelling of graphite
CN103693638A
Carbon electrode, production method thereof, and photoelectric conversion device using the same
JP2013209261A
Graphene manufacturing
JP2014513659A
A method for forming expanded hexagonal layer minerals and derivatives using electrochemical charging.
JP2015507320A
Graphene Nanoelectric Device Fabrication
US20110059599A1